THE IDENTIFICATION OF A HYDROXYLATED PYRROLIDINE DERIVATIVE FROM CASTANOSPERMUM-AUSTRALE - Nash, R; Bell, E; Fleet, G; Jones, R; Williams, J (1985)
A new pyrrolidine derivative, (2R,3S)-2-hydroxymethyl-3-hydroxypyrrolidine, has been isolated from Castanospermum australe, and identified by n.m.r. and mass spectroscopy and X-ray crystallography.